Bioactivation of phosphate rocks by indigenous phosphate-solubilizing fungi Bioaktivasi fosfat alam oleh fungi pelarut fosfat setempat - H WIDIASTUTI; Didiek H GOENADI; . TRI-PANJI; L P SANTI; P FATURACHIM; N MARDIANA; I HARIANTO; . ISROI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2000)
Ringkasan Efektivitas fungi pelarut fosfat (FPF) dalam meningkatkan kelarutan fosfor (P) fosfat alam (FA) sangat dipengaruhi oleh kesesuaian isolat fungi dengan mineralogi batuan fosfat. Satu seri percobaan laboratorium telah dilakukan untuk menetapkan potensi supernatan kultur cair (SKC) dari FPF asal tanah dan batuan tambang FA eksCileungsi dan Madura untuk meningkatkan kelarutan FA eks-Cileungsi (FAQ dan eksMadura (FAM) dalam pembuatan superfosfat yang diaktivasi secara biologi (SPab). Kegiatan penelitian meliputi: (1) seleksi pelarutan P-FPF dalam medium Pikovskaya, (2) pengujian kemampuan pelarutan P-FAC, P-FAM, P-Ca3 (PO4)z, dan P AIP04 isolat-isolat terseleksi, dan (3) optimasi pembuatan SPab dengan isolat terpilih. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan dua ulangan. Dari hasil isolasi diperoleh 50 isolat FPF, 17 isolat di antaranya berpotensi dalam melarutkan fosfat yang ditandai pembentukan zona bening yang intensif di sekitar koloni. Dari ketujuh belas isolat tersebut sepuluh isolat berasal dari Lulut (Cileungsi), dan tujuh isolat lainnya berasal dari Madura (masing-masing dua isolat dari Socah dan Aengnyior serta tiga isolat dari Korbe). Berdasarkan kemampuan melarutkan P dari FAC, FAM, Ca3(PO4)2, dan AIP04 diperoleh masing-masing tiga isolat dari Cileungsi dan Madura. Dari keenam isolat tersebut empat isolat di antaranya tergolong Penicillium sp. dan dua isolat lainnya termasuk Aspergillus sp. Di antara keenam isolat tersebut isolat Korbe 0909 memiliki kemampuan iertinggi dalam melarutkan P dari semua sumber P. Kandungan P-FAC lebih tinggi daripada FAM dan mendekati FA eks Maroko. SKC dapat menggantikan fungsi H2SO4 (98%) dalam melarutkan P-FA. SPab Cileungsi mengandung P nyata lebih tinggi daripada FAC yang diaktivasi secara konvensional, namun pada SPab Madura kandungan P larut air nyata lebih rendah, sedangkan P larut asam sitrat 2% dan perklorat sebanding dengan FAM yang diaktivasi secara konvensional. Aktivasi FA oleh SKC dapat menurunkan konsentrasi asam fosfat (H3PO4) dari 52% menjadi 42%. Kelarutah P (asam sitrat 2% dan air) dan kandungan sulfur-SPab Cileungsi dan Madura nyata lebih rendah dibandingkan dengan SP36.Summary The effectiveness of phosphate-solubilizing fungi (PSF) in enhancing phosphorus (P) solubility of phosphate rocks (PR) is assumed to be dependent on the suitability of the fungal isolate to the mineralogycal composition of the rocks. A laboratory study was conducted to determine the phosphate solubilizing ability of liquid culture supernatants (LCS) of PSF isolated from various PR deposits and adjacent soils, i.e. at Cileungsi in West Java and the island of Madura in East Java to enhance the reactivity of PR from deposits at Cileungsi (CPR) and Madura (MPR) and their potential use as agents in the production of biologically-activated superphosphate (SPab). Three series of laboratory experiments were conducted: (1) screening isolate on the solubilization of P in Pikovskaya medium; (2) assaying the ability of selected isolates on solubilization of P-CPR, PMPR, P-Ca3(P04)2 and P-AIPO4, and (3) optimizing superphosphate fertilizer formulation. Completely random design was used as the experimental design with two replicates. Seventeen out of 50 PSF isolates were characterized to be highly potential as phosphate solubilizers, as indicated by clear zone formation. Ten isolates were from Lulut (Cileungsi) and seven from Madura island, two from Socah and Aengnyior respectively, and remaining three from Korbe. Regarding the ability of P solubilization of four P sources, six isolates were selected, three each from Cileungsi and Madura. Of these six isolates, four are Penicillium sp., and four belong to Aspergillus sp. The Aspergillus sp. isolate Korbe 0909 was found to be the highest in P-solubilization of various sources of P. Based on the P dissolving ability of P-CPR and their effectiveness in substituting for sulphuric acid (98%) usually used in conventional production of superphosphate, the LCS of Korbe 0909 improved significantly the P-PRs dissolution. MPR activated by the LCS yielded a comparable values of 2% citric acid-soluble P content and significantly lower water-soluble P compared with conventional method: Reduction of phosphoric acid (H3PO4) concentration from 52% to 42%, in combination with LCS treatment, produced P dissolution comparable to the conventional method. Although the P solubilization of CSPab and MsPab in both 2% citric acid and water as well as thus content were significantly lower compared with SP36.